The role of mineral fertilizers in transforming Philippine agriculture - Briones, Roehlano M. (International Food Policy Research Institute, 2014)
Fertilizer policy in the country has evolved from pervasive interventionism in the 1970s to today's market-oriented regime. Government has abandoned price policies and subsidies, focusing rather on standard-setting, quality regulation, and train-ing. Over the same period domestic demand for fertilizer has continually been increasing, though recently resurgent fertilizer prices has reduced total utilization. Evidence suggests that farmers are under-applying fertilizer, thereby forfeiting efficiency gains at the margin. On the supply side, imports have in the past few decades emerged as the main source of fertilizer, as domestic production has dwindled. With deregulation, numerous private sector players have taken over the distribution of fertilizers; analysis of the supply chain points to low marketing margins. Integration analysis fails to find systematic arbitrage opportunities between the domestic and world markets. Within the domestic market however, there remain large disparities in prices across regions. Priorities for research and policy are therefore understanding the behavior of farmers in terms of fertilizer application, and addressing internal price disparities, perhaps by improved transport infrastructure and logistics.